Sosialisasi, Mobilisasi Dan Keterlibatan Kelompok Sasaran Dalam Program Pelayanan Ims Di Puskesmas Kabupaten Sukoharjo - Surati Ningsih - Poltekkes Bhakti Mulia (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2018)
Abstract : Â Cases of HIV and AIDS in Sukoharjo district based on the risk group in 2014 which was found 2 cases in WPS group, transvestites 6 cases, LSL 27 cases, 12 cases of customer and partner 9 cases. Sukoharjo Regency Health Office has established two health centers as sexually transmitted infections (STI) clinics, this study aims to analyze the organisation of STI program in Sukoharjo public Health Center. This research is qualitative using in-depth interviews. Key informants were eight officers executing the program is doktor, nurse/midwife, laboratorium officer and administrative officer. Informant triangulation is the head of public health center, head of P2 department on DKK and key population. The data analysis techniques are by analyzing the content, including in-depth interviews with informants, it was processed and then the data were analyzed.The results showed that the socialization of STI service program through cooperation with NGOs, the mobilization of STI services in puskesmas and mobile clinic STI has not been running optimally and transgender groups tend to be more actively involved in the implementation of STI program.The proposed recommendation is to the Sukoharjo District Health Office coordinate with local religious leaders and communicate continuously with health professional organizations, social organizations, alert villages, peer educators and AIDS Awareness Residents to motivate key populations to come to STI service health centers. The frequency of cross-program and cross-sector socialization is further enhanced, as well as increasing commitment and performance in implementing STI services.Keywords : Socialization, Mobilization, Target Group Involvement, IMS Service ProgramÂ Â Abstrak : Kasus HIV dan AIDS di kabupaten Sukoharjo berdasarkan kelompok resiko didapatkan pada kelompok WPS sebanyak 2 kasus, waria 6 kasus, LSL 27 kasus, pelanggan 12 kasus dan pasangan risti 9 kasus. Penelitian ini bertujuan untuk menganalisis pelaksanaan sosialisasi, mobilisasi dan keterlibatan kelompok sasaran dalam program pelayanan IMS Puskesmas Kabupaten Sukoharjo.Jenis penelitian ini adalah kualitatif dengan menggunaka nwawancaramendalam. Informan utama dalam penelitian ini adalah delapan petugas pelaksana program yaitu dokter, perawat / bidan, petugas laboratorium dan perugas administrasi. Informan triangulasi kepala puskesmas, Kasi P2 DKK dan Populasi Kunci. Teknik analisis data dengan analisis konten, meliputi wawancara mendalam dengan informan diolah kemudian dilakukan analisis data.Hasil penelitian menunjukkan bahwa sosialisasi program pelayanan IMS melalui kerjasama dengan LSM, mobilisasi berupa pelayanan IMS di puskesmas maupun mobile clinic IMS belum berjalan optimal dan kelompok waria cenderung lebih aktif terlibat dalam pelaksanaan program IMS.Saran direkomendasikan kepada Dinas Kesehatan Kabupaten Sukoharjo berkoordinasi dengan tokoh agama setempat dan melakukan komunikasi secara terus menerus dengan organisasi profesi kesehatan, organisasi sosial, desa siaga, peer educator dan Warga Peduli AIDS (WPA) untuk memotivasi populasi kunci datang ke Puskesmas pelayanan IMS. Frekuensi sosialisasi lintas program dan lintas sektor lebih ditingkatkan, serta meningkatkan komitmen dan kinerja dalam melaksanakan pelayanan IMS Kata kunci: Sosialisasi, Mobilisasi, Keterlibatan Kelompok Sasaran, Program Pelayanan IMS